Modeling of changes in particle size distribution of solids in multistage separation systems - Lagereva E.A. (Научно-технический вестник Брянского государственного университета)
The presented method of calculation of the separation of solid particles from gas streams to multistage separation sys-tems, consisting of a number of sequentially installed separational devices of various design and principle of operation. It is based on a separate analysis of the sequential processes of capture and transmission of individual fractions of solid particles of a polydisperse structure. The technique provides information about changes in particle size distribution of solids with the passage of the gas flow in the treatment system and allows you to specifically select the effective combination of different types of separators.